MOESM1 of Estimation of breeding values for uniformity of growth in Atlantic salmon (Salmo salar) using pedigree relationships or single-step genomic evaluation - Panya Sae-Lim; Kause, Antti; Lillehammer, Marie; Mulder, Han (Figshare, 2017)
Additional file 1: Figure S1. Estimated breeding values for standardized body weight and its uniformity based on sire-dam DHGLM. The data provided represent the boxplot of estimated (genomic) breeding values of genotyped animals based on sire-dam DHGLM when using pedigree (A) or combined pedigree and genomic relationships (H).